Rekonstruksi Kebijakan Jual Beli Tanah Bersertifikat dalam Bentuk Non-Fungible Token Melalui Aplikasi Marketplace - Jaya, Rania Pramesti; Nurwidhiyanti, Hanif; Jauharoh, Arini (Universitas Negeri Malang, 2023)
The purpose of writing this article isto analyze the validity and legal protection of buying and selling certified land in the form of non-fungible tokens through a marketplace application. This study uses a normative juridical method with a statutory and regulatory approach and a contextual approach. Buying and selling certified land in the form of non-fungible tokens through a marketplace application is a policy reconstruction that can be realized. The sale and purchase of certified land in the form of non-fungible tokens through the marketplace application has fulfilled the legal requirements for a sale and purchase agreement as regulated in Article 1320 of the Civil Code and Article 46 paragraph (2) of Government Regulation Number 71 of 2019, namely the existence of agreement, skill , objects and causes that do not conflict with morality, consent and laws and regulations. The legal protection that can be provided to the parties is preventive legal protection in the form of an electronic land certificate represented in the form of a non-fungible toke